Peran Komunikasi Antarpribadi dalam Resolusi Konflik Antar Karyawan di Organisasi Perusahaan - April Laksana; Hani Nur Rizka; Defika Lailatul Nur Khasanah; Muawanah Aliyah (Kajian Administrasi Publik dan ilmu Komunikasi, 2024)
This study aims to analyze the role of interpersonal communication in conflict resolution between employees in corporate organizations. The results of the study indicate that conflict is often caused by unclear instructions, misunderstandings in conveying messages, and emotional factors such as frustration and personal tension. However, effective interpersonal communication, such as active listening, expressing feelings without blaming, and an open attitude, have been shown to help resolve conflicts constructively. In addition, organizational culture plays an important role in influencing conflict resolution styles. In organizations with an open and collaborative communication culture, approaches such as negotiation and compromise are more often applied, resulting in mutually beneficial solutions. In contrast, more hierarchical organizations tend to avoid conflict or use coercion, which often results in dissatisfaction. This study emphasizes the importance of developing interpersonal communication skills and an organizational culture that supports openness to create a harmonious and productive work environment.